Unraveling the efficiency of heteroatom-doped graphene quantum dots incorporated MOF-derived bimetallic layered double hydroxide towards oxygen evolution reaction. (5th November 2022) - Rinawati, Mia; Wang, Yu-Xuan; Huang, Wei-Hsiang; Wu, Yu-Ting; Cheng, Yao-Sheng; Kurniawan, Darwin; Haw, Shu-Chih; Chiang, Wei-Hung; Su, Wei-Nien; Yeh, Min-Hsin
Abstract: Addressing energy and environmental issues, developing highly efficient, durable, and earth-abundant, electrocatalysts are crucial in oxygen evolution reaction (OER) for energy conversion and storage. Extensive research about the metal-organic framework (MOF) derived layered double hydroxides (LDH) and carbon-based electrocatalysts have been devoted, despite the exceptional performance in OER, yet the limited exposed active sites remain a challenge. Therefore, we reported a novel heteroatom-doped graphene quantum dots (GQDs) incorporated into MOF-derived NiFe-LDH. Taking advantage of abundant active and edge sites of GQDs and modifying the surface chemistry by chemical doping with foreign atoms, the designed heteroatom-doped GQDs/MOF-derived LDH exhibited superior catalytic performance low overpotential of 251 mV at a current density of 100 mA cm −2 in alkaline media. Our result confirmed the synergistic effect between the doped heteroatom and the uttermost exposure of heteroatom-doped GQDs/MOF-derived LDH's active sites on its surface, providing swift reactant's transportation and adequate contact for improving the OER performance. Graphical abstract: Image 1 Highlights: A novel hybrid heteroatom-doped GQDs/MOF-derived LDH electrocatalyst has been developed. The relationship between single and dual-doped GQDs in OER activity has been explored and optimized. Synergistic effect of N and B dopants within GQDs significantly improves the OER performance. B, N-GQDs/MOF-derived NiFe LDH exhibits superior electrocatalytic OER performance (η100  = 251 mV).